Molecular Analysis of CYP27B1 Mutations in Vitamin D-Dependent Rickets Type 1A: c.590G > A (p.G197D) Missense Mutation Causes a RNA Splicing Error - Zou, Minjing; Guven, Ayla; BinEssa, Huda A.; Al-Rijjal, Roua A.; Meyer, Brian F.; Alzahrani, Ali S.; Shi, Yufei (Frontiers in Genetics, 2020)
Context: Vitamin D-dependent rickets type 1A (VDDR-IA) is a rare autosomal recessively inherited disorder due to loss-of-function mutations in the CYP27B1 gene. CYP27B1 encodes an enzyme of 25-hydroxyvitamin D-1α-hydroxylase for converting inactive 25-OHD to biologically active 1,25-(OH)2D. Objective: To identify underlying genetic defects in patients with VDDR1A. Methods: Twelve patients from 7 Turkish and 2 Saudi families were investigated. The coding exons and intron-exon boundaries of the CYP27B1 gene were amplified by Polymerase Chain Reaction (PCR) from peripheral lymphocyte DNA. PCR products were directly sequenced. The consequences of c.590G>A mutation were analyzed by in-silico and functional analysis. Results: CYP27B1 mutations were identified in all the patients. Two novel mutations were identified in two separate families: c.171delG (family 7) and c.398_400dupAAT (family 8). The intra-exon deletion of c.171delG resulted in a frameshift and premature stop codon 20 amino acids downstream from the mutation (p.L58Cfs*20). The intra-exon duplication of c.398_400dupAAT generated a premature stop codon at the mutation site (p.W134*). A missense c.590G>A (p.G197D) mutation was found in a patient from family 4 and caused a defect in pre-mRNA splicing. As a result, two populations of transcripts were detected: the majority of them with intron 3 retention (83%), and the minority (17%) being properly spliced transcripts with about 16% of wild-type enzymatic activity. The remaining 9 patients from 6 families carried a previously reported c.1319_1325dupCCCACCC (F443Pfs*24) mutation. Clinically, all the patients need continued calcitriol treatment, which was consistent with inactivation of 25-hydroxy vitamin D1α-hydroxylase activity. Conclusions: Two novel frameshift CYP27B1 mutations were identified and predicted to inactivate 25-hydroxyvitamin D-1α-hydroxylase. The loss of enzymatic activity by c.590G>A missense mutation was mainly caused by aberrant pre-mRNA splicing.